Managing digital cultural objects analysis, discovery and retrieval - Foster, Allen 1968-; Rafferty, Pauline 1959- (Facet Publishing, 2016)
This book explores the analysis and interpretation, discovery and retrieval of a variety of non-textual objects, including image, music and moving image. Bringing together chapters written by leading experts in the field, this book provides an overview of the theoretical and academic aspects of digital cultural documentation and considers both technical and strategic issues relating to cultural heritage projects, digital asset management and sustainability. Managing Digital Cultural Objects: Analysis, discovery and retrieval draws from disciplines including information retrieval, library and information science (LIS), digital preservation, digital humanities, cultural theory, digital media studies and art history. It's argued that this multidisciplinary and interdisciplinary approach is both necessary and useful in the age of the ubiquitous and mobile Web.